Behaviour of concrete-filled ferritic stainless steel tubular joints: Experimental investigation, numerical modelling and design. (15th November 2021) - Li, Hai-Ting; Young, Ben
Highlights: A total of 196 new concrete-filled ferritic stainless steel tubular (CFFSST) joint results are reported. CIDECT provisions exhibit remarkable scatter predictions for the CFFSST joints. Existing design rules are generally not accurate for the CFFSST joints. Improved design rules are proposed to predict the capacities of CFFSST X-and T-joints. Abstract: The behaviour and resistances of concrete-filled ferritic stainless steel tubular (CFFSST) joints were studied and presented in this paper based upon experimental and numerical investigations. A test program was firstly undertaken on a series of X- and T-joints with square and rectangular hollow section (SHS and RHS) chords. The stainless steel SHS/RHS tubes were cold-rolled from EN 1.4003 ferritic grade sheets, and the specimens were in-filled with either normal or high strength concrete. The experimental study including the detailed material properties, joint test setups, test procedures and results is reported. Numerical models were also developed and verified against the CFFSST joint test results, and followed by a parametric study generating further numerical results over a wider range of key joint parameters. The obtained experimental and numerical CFFSST joint capacities were compared with existing design recommendations as per the CIDECT Design Guide and design rules proposed by previous researchers. The comparison results indicate that the existing provisions are not capable of predicting the capacities of the investigated composite tubular joints in an accurate and reliable manner. Hence, modified design rules are put forward in this paper for the design of CFFSST joints.